Active Dosimetry with the Ability to Distinguish Pulsed and Non-Pulsed Dose Rate Contributions - Makarevich Krystsina (EDP Sciences, 2021)
This paper presents the concept of an active dosimetry system and its operational regime for pulsed radiation dose rate measurements. The plastic scintillator is suggested to be used for absorbed dose rate measurements. As long as the detector can be considered tissue equivalent, the energy weighting of pile-up events in terms of the dose is achieved. The real-time distinction of pulsed and non-pulsed dose rate contributions is based on the time structure of a single interaction and requires only basic information about the beam time structure (pulses duration and period). The detector connected to a fully digital signal processing board creates an active dosimetry system with adjustable parameters. Such a system was used for absorbed dose rate measurements in pulsed photon field mimicking radiation field outside the bunker of a medical LINAC, but also in the presence of a constant radiation component. The results show a linear dependence of a pulsed radiation contribution on the accelerator current in the investigated range of the total dose rate up to 8 μGy/h.